The New Eco‐Schemes: Navigating a Narrow Fairway. (19th April 2022) - Latacz‐Lohmann, Uwe; Termansen, Mette; Nguyen, Chi
Summary: This article highlights some key challenges and trade‐offs with which national policy designers have to contend in devising national eco‐schemes for agriculture. We show that policy designers operate in a narrow design space which is constrained by various political and legal requirements. One key challenge is to design a reward system that allows the uptake of eco‐schemes by farmers to be aligned with a given budget. We present four broad implementation models for eco‐schemes and discuss their merits and shortcomings in light of stipulated requirements. These are the 'greening model', the 'modified greening model', the 'eco‐points model' and the 'AECS model' in the style of the agri‐environmental and climate schemes of CAP Pillar 2. We conclude that the eco‐points model is likely to be the most suitable. By stipulating that individual farmers must reach a certain minimum number of points per hectare (eligibility threshold), but are not entitled to payments for points that exceed a certain upper limit per hectare (cut‐off), it allows demand from farmers for inclusion in a scheme to be steered such that aggregate uptake coincides with the budget; thereby reducing the risk of over‐ or under‐subscription while maintaining flexibility to cater for heterogeneity in site conditions. Abstract : Cet article met en évidence certains défis et compromis majeurs auxquels les concepteurs des politiques nationales doivent faire face lors de l'élaboration des éco‐régimes nationaux pour l'agriculture. Nous montrons que ces concepteurs opèrent dans un espace étroit qui est contraint par diverses exigences politiques et juridiques. L'un des principaux défis consiste à concevoir un système de récompense qui permette d'aligner l'adoption des écorégimes par les agriculteurs sur un budget donné. Nous présentons quatre grands modèles de mise en œuvre pour les écorégimes et examinons leurs mérites et leurs lacunes à la lumière des exigences stipulées. Il s'agit du 'modèle de verdissement', du 'modèle de verdissement modifié', du 'modèle par éco‐points'et du 'modèle SAEC' dans le style des schémas agri‐environnementaux et climatiques du pilier 2 de la PAC. Nous en tirons la conclusion que le modèle par éco‐points est probablement le plus approprié. En stipulant que les agriculteurs individuels doivent atteindre un certain nombre minimum de points par hectare (seuil d'éligibilité), mais qu'ils n'ont pas droit aux paiements pour les points qui dépassent un certain plafond par hectare (seuil), il permet de piloter la demande des agriculteurs d'inclusion dans un écorégime de manière à ce que la participation totale coïncide avec le budget ; réduisant ainsi le risque de sur‐ ou de sous‐souscription tout en conservant la flexibilité nécessaire pour répondre à l'hétérogénéité des conditions locales. Abstract : In diesem Artikel werden einige der größten Herausforderungen und Kompromisse hervorgehoben, mit denen sich Politikgestaltende bei der Ausarbeitung nationaler Eco‐Schemes für die Landwirtschaft auseinandersetzen müssen. Wir zeigen, dass der Gestaltungsspielraum durch verschiedene politische und rechtliche Anforderungen begrenzt ist. Eine zentrale Herausforderung besteht darin, ein Belohnungssystem zu entwerfen, das es den landwirtschaftlichen Betrieben ermöglicht, die Inanspruchnahme von Eco‐Schemes mit einem bestimmten Budget in Einklang zu bringen. Wir stellen vier Modelle für deren Umsetzung vor und erörtern ihre Vor‐ und Nachteile m Hinblick auf die festgelegten Anforderungen. Es handelt sich dabei um das "Greening‐Modell", das "modifizierte Greening‐Modell", das "Ökopunkte‐Modell" und das "AECS‐Modell", in Anlehnung an die Agrarumwelt‐ und Klimaregelungen der zweiten Säule der GAP. Wir kommen zu dem Schluss, dass das Ökopunkte‐Modell wahrscheinlich am ehesten geeignet ist. Danach wird festgelegt, dass ein landwirtschaftlicher Betrieb eine bestimmte Mindestanzahl von Punkten pro Hektar erreichen muss (Förderfähigkeitsschwelle). Allerdings hat der Betrieb keinen Anspruch auf Zahlungen für Punkte, die eine bestimmte Obergrenze pro Hektar überschreiten (Abschneidegrenze). Auf diese Weise ist es möglich, die Nachfrage nach einzelnen Maßnahmen zu steuern und eine Übereinstimmung mit dem vorhandenen Budget zu erreichen. Dadurch wird das Risiko einer Über‐ oder Unterzeichnung verringert, während gleichzeitig die Flexibilität erhalten bleibt, um die Heterogenität der Standortbedingungen zu berücksichtigen.